2023
DOI: 10.1371/journal.pone.0295058
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of nitrate-reducing and highly abundant microbial communities in the oral cavity

Joanna E. L’Heureux,
Mark van der Giezen,
Paul G. Winyard
et al.

Abstract: The nitrate (NO3-) reducing bacteria resident in the oral cavity have been implicated as key mediators of nitric oxide (NO) homeostasis and human health. NO3--reducing oral bacteria reduce inorganic dietary NO3- to nitrite (NO2-) via the NO3--NO2--NO pathway. Studies of oral NO3--reducing bacteria have typically sampled from either the tongue surface or saliva. The aim of this study was to assess whether other areas in the mouth could contain a physiologically relevant abundance of NO3- reducing bacteria, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When reaching the salivary glands, nitrate is secreted by active transport from blood into saliva, achieving salivary nitrate levels up to 20-times the plasma level. In the oral cavity, salivary nitrate is partially converted into nitrite by oral and commensal microbial reductases (Eisenbrand et al 2022 ; Eisenbrand et al 1980 ; L’Heureux et al 2023 ; Liu et al 2023 ). Approximately 25% of the orally ingested nitrate is secreted through the salivary glands and up to 7–8% of the totally ingested nitrate becomes converted to nitrite in the oral cavity during entero-salivary circulation (Spiegelhalder et al 1976 ; Tannenbaum et al 1976 ; Tricker and Preussmann 1987 ).…”
Section: Exposure To N -Nitrosating Agents: the Co...mentioning
confidence: 99%
“…When reaching the salivary glands, nitrate is secreted by active transport from blood into saliva, achieving salivary nitrate levels up to 20-times the plasma level. In the oral cavity, salivary nitrate is partially converted into nitrite by oral and commensal microbial reductases (Eisenbrand et al 2022 ; Eisenbrand et al 1980 ; L’Heureux et al 2023 ; Liu et al 2023 ). Approximately 25% of the orally ingested nitrate is secreted through the salivary glands and up to 7–8% of the totally ingested nitrate becomes converted to nitrite in the oral cavity during entero-salivary circulation (Spiegelhalder et al 1976 ; Tannenbaum et al 1976 ; Tricker and Preussmann 1987 ).…”
Section: Exposure To N -Nitrosating Agents: the Co...mentioning
confidence: 99%
“…Salivary glands absorb 25% of nitrate in food, and nitrate is formed by endogenous oxidation. Symbiotic bacteria in the mouth produce nitrate reductase, metabolize NO3− in saliva to NO2−, and help the host complete the first step of the NO conversion process ( 98 ). Another study has shown that periodontal pathogens can reduce the synthesis of NO and tetrahydrobiopterin (BH4) in mice, which is a cofactor of nitric oxide synthetase (NOS), and its reduction will lead to a decrease in NOS and NO synthesis in blood vessels and colon ( 99 ).…”
Section: Interaction Between Oral Bacteria and Gut Bacteriamentioning
confidence: 99%